2019
DOI: 10.3389/fphys.2019.00576
|View full text |Cite
|
Sign up to set email alerts
|

Stumbling Reactions in Partial Gravity – Neuromechanics of Compensatory Postural Responses and Inter-Limb Coordination During Perturbation of Human Stance

Abstract: Spontaneous changes in gravity play a significant role in interplanetary space missions. To preserve the astronauts’ capability to execute mission-critical tasks and reduce the risk of injury in transit and on planetary surfaces, a comprehensive understanding of the neuromuscular control of postural responses after balance deterioration in hypo- or hyper-gravity conditions is essential. Therefore, this study aimed to evaluate the effect of acute gravitational variation on postural adjustments in response to pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 71 publications
(116 reference statements)
1
1
0
Order By: Relevance
“…Muscle activations were lower during the arm movements in microgravity and higher in hypergravity with respect to the corresponding muscle activations in normogravity. This is in line with a previous study where they showed that increased environmental gravity increases EMG amplitudes (Ritzmann et al, 2019 ). Changes in muscle activations were observed in deltoid anterior, deltoid posterior, and trapezius for movements in both directions.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Muscle activations were lower during the arm movements in microgravity and higher in hypergravity with respect to the corresponding muscle activations in normogravity. This is in line with a previous study where they showed that increased environmental gravity increases EMG amplitudes (Ritzmann et al, 2019 ). Changes in muscle activations were observed in deltoid anterior, deltoid posterior, and trapezius for movements in both directions.…”
Section: Discussionsupporting
confidence: 94%
“…The main purpose of this study was to investigate if local gravity compensation could mitigate the well-known changes to arm movements caused by novel gravitational environments (Tafforin et al, 1989 ; Bock et al, 1992 , 1996 ; Fisk et al, 1993 ; Berger et al, 1997 ; Papaxanthis et al, 2005 ; Ritzmann et al, 2019 ). In fact, the altered environmental gravity during our experiment significantly affected most of the observed parameters of arm movements with respect to normogravity.…”
Section: Discussionmentioning
confidence: 99%